Associations between frequencies of a susceptible TNF-α promoter allele and protective α-thalassaemias and malaria parasite incidence in vanuatu. - Ubalee, R.; Tsukahara, T.; Kikuchi, M.; Lum, J.K.; Dzodzomenyo, M.; Kaneko, A.; Hirayama, K. (My University, 2005)
Tumour necrosis factor-alpha (TNF-α) is one of the key cytokines that influence the pathology of microbial infections. The genetic susceptibility to severe forms of falciparum malaria is differentially associated with TNF-α promoter gene polymorphisms (TNFP alleles). In a previous study, we identified a TNFP-allele characterized by a C to T transition at position −857 (TNFP-D allele) as a marker for susceptibility to cerebral malaria in Myanmar. The frequencies of TNFP alleles on six islands of Vanuatu, Melanesia (South-west Pacific) were estimated to investigate whether malaria selection pressure on this susceptibility marker has influenced its prevalence. Within the archipelago of Vanuatu there is a decreasing cline of parasite incidence from North to South. Of the four alleles of the TNFP gene detected in Vanuatu, the TNFP-D allele frequencies were inversely correlated with the parasite incidence of islands; TNFP-D varied from 0.55 on the island with the lowest parasite incidence to 0.26 on the island with the highest parasite incidence (r = −0.855, P = 0.03). We also observed a significant correlation between the frequencies of α-thalassaemia alleles, thought to protect against malaria and parasite incidence in the same populations. These data are consistent with a previously reported correspondence between the frequencies of glucose 6-phosphate dehydrogenase (G6PD) deficiency and parasite incidences on the islands of Vanuatu (Kaneko et al. 1998) and indicate that the degree of malaria endemicity has influenced the allele frequencies of at least three loci that confer both susceptibility (TNFP-D) and protection (α-thalassaemias and G6PD deficiency).
Keywords: malaria; selection; TNF-α; α-thalassaemia; Melanesia